Chrysopilus (Diptera: Rhagionidae) from Brazil: redescription of Chrysopilus fascipennis Bromley and description of eleven new species - Santos, Charles Morphy D.; de Souza Amorim, Dalton (Zootaxa, 2007)
Chrysopilus Macquart is the most diverse genus of Rhagionidae (Diptera, Brachycera), widespread in distribution, encompassing all biogeographical regions. A taxonomic revision of the Brazilian Chrysopilus is made, with the description of 11 new species – C. balbii sp. n., C. caligatus sp. n., C. camargoi sp. n., C. capillosus sp. n., C. hyalinus sp. n., C. microphallus sp. n., C. orphnopterus sp. n., C. phaeopterus sp. n., C. plaumanni sp. n., C. semipictus sp. n., and C. vitreus sp. n. – and the redescription of C. fascipennis Bromley.